1993
DOI: 10.1007/bf02536057
|View full text |Cite
|
Sign up to set email alerts
|

Nervonic acid in red blood cell sphingomyelin in premature infants: An index of myelin maturation?

Abstract: The present study addresses the question whether nervonic acid (24:1n-9) accumulation in sphingomyelin (SM) of red blood cells (RBC) could yield information on cerebrum maturation in premature infants. The study included 28 premature eutrophic infants of 31.5 wk gestational age. Eleven were fed with human milk, nine with a regular formula and eight with an alpha-linolenate-enriched formula. The fatty acid composition of the SM fraction was determined by gas-liquid chromatography on a 50-m fused silica capillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…It has been reported that fatty acids esterified to erythrocyte membrane phospholipids closely reflect those of neuronal membranes (Carlson et al, 1986;Babin et al, 1993). Nevertheless, adipose tissue fatty acids also may be related to brain fatty acids (Christensen and Hoy, 1997;Valenzuela et al, 2004;Taha et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that fatty acids esterified to erythrocyte membrane phospholipids closely reflect those of neuronal membranes (Carlson et al, 1986;Babin et al, 1993). Nevertheless, adipose tissue fatty acids also may be related to brain fatty acids (Christensen and Hoy, 1997;Valenzuela et al, 2004;Taha et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The speed of information processing by myelinated nerve fibres is significantly faster than that by unmyelinated nerve cells. It has been reported that feeding SM fortified milk promoted the myelination of the cortex in the rat [26]. Polyunsaturated fatty acids (e.g., DHA) have important roles in the fluidity of neurons of the brain, which influences signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingomyelin (SM) plays an important role in the structure of the brain cell membrane [26]. The SM molecule consists of a phosphocholine polar head group and a sphingosine backbone, and is classified as a sphingolipid.…”
Section: Introductionmentioning
confidence: 99%
“…0.05). This decline appeared at a time when cerebral maturation was in rapid progression, with probably a high uptake/consumption of 18:1 n-9 for the synthesis of nervonic acid required for myelination [29]. Therefore, attention should be drawn to the supply of 18:1 n-9 or its 18:0 precursor since endogenous biosynthesis is not able to compensate for absence of dietary oleic acid, at least in peripherical tissues [30].…”
Section: Resultsmentioning
confidence: 99%